Ethanolic Leaves Extracts of Calatropis procera (Aiton) Leaves as Potential Corrosion Inhibitor for Mild Steel in HCl Solution - A. M. Lawal; I. Mudi; K. Kabir; A. Muhammad (Journal of Applied Sciences and Environmental Management, 2022)
The Calotropis procera leaves extract (CPLE) was investigated as a potential corrosion inhibitor for mild steel in HCl solution using the thermometric technique. The phytochemical screening showed that tannins, saponins, flavonoids, steroids glycosides, and resins were all present in the leaves extract. Results of this work reveal that corrosion rate of mild steel in HCl is proportionally related to the acid concentration. Additionally, it was also found that inhibition efficiency (%I) increased with the increase in the concentration of leaf extracts, which directly led to a decrease in corrosion reaction number. It was determined that an ethanolic extract of Calotropis procera may be a good candidate for preventing mild steel corrosion in an acidic environment owing to the significant number of phytochemical compounds that the extract contained, and its ability to achieve an inhibition efficiency of up to 82.99%.